1984
DOI: 10.1007/bf02014331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six methods for detecting human rotavirus in stools

Abstract: The following six methods for detecting rotavirus in human faecal samples were compared: electron microscopy, immune electron microscopy, immunofluorescence in cell culture, two enzyme immunoassays (Rotazyme, Enzygnost ) and a latex agglutination test ( Rotalex ). Specimens were collected from 112 children with diarrhoea. The relative sensitivities of the different assays for human rotavirus were as follows: electron microscopy, 84%; immunofluorescence, 86%; Rotalex , 88%; Rotazyme, 89%; immune electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
(22 reference statements)
5
24
1
1
Order By: Relevance
“…In summary, it turned out that the EIAs were equivalent with respect to their sensitivities and were comparable or even slightly superior to EM. This is in concordance with the majority of publications covering this subject (4,5,8,12,13,15,17,18). Some investigators have postulated that EIAs are probably a better standard method for detection of rotaviruses than is EM due to the low sensitivity of the latter (2, 5); however, in these studies EM was performed without ultracentrifugation of samples, which has been demonstrated to be an essential step in achieving maximum sensitivity (7).…”
Section: %]) Because the Pathfinder Test Issupporting
confidence: 68%
“…In summary, it turned out that the EIAs were equivalent with respect to their sensitivities and were comparable or even slightly superior to EM. This is in concordance with the majority of publications covering this subject (4,5,8,12,13,15,17,18). Some investigators have postulated that EIAs are probably a better standard method for detection of rotaviruses than is EM due to the low sensitivity of the latter (2, 5); however, in these studies EM was performed without ultracentrifugation of samples, which has been demonstrated to be an essential step in achieving maximum sensitivity (7).…”
Section: %]) Because the Pathfinder Test Issupporting
confidence: 68%
“…The grids were examined with a Jeol-Jem-100S electron microscope (Japanese Electron Optics, Beabody, Mass., U.S.A.) at a magnification of 40 000X. A latex agglutination (LA) method was used to detect rotavixus antigen (Haikala et al, 1983;Morinet et al, 1984): 20 u[ of the fecal suspension from each sample was mixed with an equal amount of LA reagent on a glass slide from each sample. Negative controls were also made.…”
Section: Virologymentioning
confidence: 99%
“…These include enzyme-linked immunosorbent assays (EIA or ELISA), radioimmunoassay (RIA), latex particle agglutination (LA), and immunofluorescence (IF). Several com parisons of these assays with regard to sensitivity, specificity, and positive and negative predictive values have been reported (55)(56)(57). In these com parisons the detection methods employing anti-rotavirus antibody, par ticularly EIA, have proven more sensitive than EM, although not necess arily more sensitive than IBM.…”
Section: Diagnostic Methodsmentioning
confidence: 99%